Unified architecture of single-phase active power filter with battery interface for UPS operation - Sousa, Tiago J. C. (2017)
This paper presents a shunt active power filter with battery interface for uninterruptible power supply (UPS) operation. The proposed unified architecture is composed by a single-phase ac-dc converter from the power grid side and by a bidirectional isolated dc-dc converter to interface the batteries, allowing the operation in three distinct modes: (1) Shunt active power filter; (2) Off-line UPS to supply a set of priority loads during power outages; (3) Energy storage system to support the power grid. The proposed architecture and the developed control algorithms were validated with a reduced-scale laboratorial prototype in all the three different operation modes. The presented experimental results highlight the benefits of the proposed architecture.